Human RECQL4 represses the RAD52‐mediated single‐strand annealing pathway after ionizing radiation or cisplatin treatment. Issue 11 (6th October 2019) - Kohzaki, Masaoki; Ootsuyama, Akira; Sun, Lue; Moritake, Takashi; Okazaki, Ryuji
Abstract : Ionizing radiation (IR) and cisplatin are frequently used cancer treatments, although the mechanisms of error‐prone DNA repair‐mediated genomic instability after anticancer treatment are not fully clarified yet. RECQL4 mutations mainly in the C‐terminal region of the RECQL4 gene lead to the cancer‐predisposing Rothmund–Thomson syndrome, but the function of RECQL4ΔC (C‐terminus deleted) in error‐prone DNA repair remains unclear. We established several RECQL4ΔC cell lines and found that RECQL4ΔC cancer cells, but not RECQL4ΔC nontumorigenic cells, exhibited IR/cisplatin hypersensitivity. Notably, RECQL4ΔC cancer cells presented increased RPA2/RAD52 foci after cancer treatments. RECQL4ΔC HCT116 cells exhibited increased error‐prone single‐strand annealing (SSA) activity and decreased alternative end‐joining activities, suggesting that RECQL4 regulates the DNA repair pathway choice at double‐strand breaks. RAD52 depletion by siRNA or RAD52 inhibitors (5‐aminoimidazole‐4‐carboxamide‐1‐β‐D‐ribofuranoside [AICAR], (−)‐epigallocatechin [EGC]) or a RAD52‐phenylalanine 79 aptamer significantly restrained the growth of RAD52‐upregulated RECQL4ΔC HCT116 cells in vitro and in mouse xenografts. Remarkably, compared to single‐agent cisplatin or EGC treatment, cisplatin followed by low‐concentration EGC had a significant suppressive effect on RECQL4ΔC HCT116 cell growth in vivo . Together, the regimens targeting the RAD52‐mediated SSA pathway after anticancer treatment may be applicable for cancer patients with RECQL4 gene mutations. Abstract : What's new? Ionizing radiation (IR) and cisplatin are frequently used cancer treatments. The mechanisms of error‐prone DNA repair‐mediated genomic instability following anticancer treatment are not fully clarified yet, however. Meanwhile, RECQL4 mutations lead to a cancer‐predisposing syndrome, but their function in error‐prone DNA repair remains unclear. Here, the authors found that IR/cisplatin‐hypersensitive RECQL4‐deficient cancer cells that are defective for alternative end‐joining stimulate RAD52‐mediated single‐strand annealing (SSA). A timed RAD52 inhibition after cisplatin treatment enhanced the tumor suppression of RECQL4‐deficient cancer cells in vitro and in vivo . The findings provide potential clinical benefits for cancer patients with RECQL4 gene mutations or upregulated RAD52.